UVC Sterilization Robot Application for Covid-19 Based on Wireless Communication - Hanalde Andre (Andalas Journal of Electrical and Electronic Engineering Technology, 2021)
In this research, a sterilization UVC robot will be designed and implemented using wireless communication. The robot can be controlled using a platform that can move the robot and is assisted by a camera to see the condition of the environment. ESP32-CAM is used to control robot via wireless communication and video assisted. The robot has two UVC lamps installed above to form a 360-degree light coverage area. The camera is at the front and is flanked by two lights to add lighting to get good video results. External antennas are used to increase the wireless communication range. The measurement results vis Wireshark obtained a delay value of 347 ms with a throughput of 358 kb/s. This value is included in the moderate category for data communication classification.